2018
DOI: 10.1177/0960327118769704
|View full text |Cite
|
Sign up to set email alerts
|

Mice pancreatic islets protection from oxidative stress induced by single-walled carbon nanotubes through naringin

Abstract: The growing use of carbon nanotubes (CNTs) emphasizes the importance of its potential toxic effects on the human health. Previous studies proved that CNTs caused oxidative stress and decreased cell viability. On the other hand, reactive oxygen species (ROS) and oxidative stress impaired β-cell functions and reduced the insulin secretion. However, there is not any study on the effects of CNTs on islets and β-cells. Therefore, the present study aimed to evaluate the effects of single-walled CNTs (SWCNTs) on oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…In priorresearch, five times higher than control levels of intracellular ROS production were seen in MWCNT-treated Rainbow Trout Liver Cell Line (RTL-W1 cells) (Simon et al, 2014). Moreover, the results of previous studies by researchers indicated that SWCNTs could induce the oxidative stress to pancreatic islets causing the occurrence of diabetes (Ahangarpour et al, 2018a). The determination of the toxic dose of MWCNTs and SWCNTs on the brain mitochondria can be a great help in terms of using these nanoparticles, especially as a medicine-bearer titles considering that the brain is a target organ for oxidative stress and according to the essential role of mitochondria in the electron transfer chain, cellular respiration, and energy production in the brain cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In priorresearch, five times higher than control levels of intracellular ROS production were seen in MWCNT-treated Rainbow Trout Liver Cell Line (RTL-W1 cells) (Simon et al, 2014). Moreover, the results of previous studies by researchers indicated that SWCNTs could induce the oxidative stress to pancreatic islets causing the occurrence of diabetes (Ahangarpour et al, 2018a). The determination of the toxic dose of MWCNTs and SWCNTs on the brain mitochondria can be a great help in terms of using these nanoparticles, especially as a medicine-bearer titles considering that the brain is a target organ for oxidative stress and according to the essential role of mitochondria in the electron transfer chain, cellular respiration, and energy production in the brain cells.…”
Section: Discussionmentioning
confidence: 99%
“…The stock suspensions were then diluted by distilled water and sonicated like before to prepare test concentrates. Three drops of Triton X-100 were then added to the volume; hence, the combination was prepared by the mitochondrial suspension (Ahangarpour et al, 2018a; Wang et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first theory postulates the generation of reactive oxygen and nitrogen species (ROS/RNS) as a consequence of injury to pleural mesothelioma cells injury due to exposure to asbestos fibers [ 42 , 43 , 44 , 45 , 46 , 47 ]. Several studies also showed the formation of free radicals, accumulation of peroxidative products and depletion of cell antioxidants in the keratinocytes and bronchial epithelial cells exposed in vitro to SWCNTs [ 48 , 49 , 50 ] and MWCNTs [ 51 , 52 , 53 , 54 , 55 ]. Like asbestos, SWCNTs/MWCNTs contain high levels of Fe, Ni, Co, Mo and other transition metal impurities which are known to induce ROS/RNS formation.…”
Section: Do Asbestos and Cnts Have The Same Mechanism Of Pathogenicity?mentioning
confidence: 99%
“…shown versatile and attractive antidiabetic activity. Caffeic acid, a known phenolic acid compound, could protect mice pancreatic islets from oxidative stress induced by multiwalled carbon nanotubes (MWCNTs) [193]. Investigation of the effect of caffeic acid and cinnamic acid on glucose uptake in TNF-R-induced insulin-resistant hepatocytes showed that they may eliminate insulin resistance by improving insulin signaling and enhancing glucose uptake in insulin-resistant cells, which described their antihyperglycemic potential [194].…”
Section: Phenolic Compounds Phenolic Compounds Havementioning
confidence: 99%